2021
DOI: 10.1044/2021_lshss-20-00119
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Written Stuttering Disclosure on the Perceptions of a Child Who Stutters

Abstract: Purpose This study measured between-groups differences in perceived speech skills and personality characteristics of a 12-year-old male child who stutters (CWS) as a function of a written factual stuttering disclosure statement, delivered by the CWS, his “mother,” or his “teacher.” Method Four hundred twenty-four college-age adults were assigned to one of four groups, including three experimental groups (i.e., written self-disclosure, mother-written dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 84 publications
0
12
2
Order By: Relevance
“…In this study, a typed disclosure statement, as if it was copied/pasted from an email, was presented to the participants. In contrast to the earlier study with verbal advocate disclosures [18], data paradoxically indicated that a written mother disclosure statement elicited more positive listener perceptions of a CWS (i.e., improved ease of listening speech skill and the calm/nervous, reliable/unreliable, and relaxed/tense personal characteristic continuum pairs), while a child written self-disclosure statement correlated to either no effect or an increased negative effect on listener perceptions of the CWS [19].…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study, a typed disclosure statement, as if it was copied/pasted from an email, was presented to the participants. In contrast to the earlier study with verbal advocate disclosures [18], data paradoxically indicated that a written mother disclosure statement elicited more positive listener perceptions of a CWS (i.e., improved ease of listening speech skill and the calm/nervous, reliable/unreliable, and relaxed/tense personal characteristic continuum pairs), while a child written self-disclosure statement correlated to either no effect or an increased negative effect on listener perceptions of the CWS [19].…”
Section: Introductioncontrasting
confidence: 99%
“…In addition, when PWS achieved a desired level of fluency, listeners typically reported that the speech sounded significantly more unnatural as a result of the therapy [17]. As a result, although traditional therapy might lessen overt stuttering frequency or severity, traditional therapy also appears to be inadequate at eradicating the observative manifestations of the disorder, including the negative consequences of stuttering on the quality of life for those who stutter [1,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations